The Effect of Rotational Speed, Draining Time, and Type of Cooking Oil on the Oil Extraction Efficiency of a Spinner Machine - Purnama, Septya Agung; Usman, Mualifi; Fahrurozi, Muhammad; Muflihah, Nur (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2025)
This study aims to determine the effects of rotational speed, drying time, and type of cooking oil on the oil draining efficiency of a spinner machine. The main issue addressed is the high residual oil content in fried food products, which negatively affects product quality and consumer health. The research was conducted using a 3x3x2 factorial experimental design, involving three levels of rotational speed (1000, 1200, 1400 rpm), three levels of draining time (5, 7, 10 minutes), and two types of cooking oil (palm oil and coconut oil). Samples of crispy mushrooms were fried and then drained using a spinner machine. Data were analyzed using a completely randomized model ANOVA (Analysis of Variance). The results show that all factors (rotational speed, draining time, and oil type) and their interactions significantly affect the de-oiling efficiency (p < 0.05). The optimal combination was achieved at 1400 rpm, 10 minutes, and using coconut oil, resulting in the highest oil-draining value of 85.31 grams. This study provides technical recommendations for improving food production efficiency with lower oil content and better product quality.